Differential prognosis of patients candidates for standard, short or prolonged dual antiplatelet treatment discharged after an acute coronary syndrome. (3rd October 2022) - Cordero, A; Escribano, D; Quintanilla, M A; Monteagudo, M; Lopez-Ayala, J M; Moreno-Arribas, J; Martinez Rey-Ranal, E; Masia, M D; Zuazola, P; Bertomeu-Gonzalez, V
Abstract: Background: Current evidence supports the efficacy of prolonged dual antiplatelet treatment prolonged (DAPT) patients at high-ischemic risk and low bleeding risk. In contrast, several trials have demonstrated the efficacy and safety of short DAPT (1, 3 o6 months) in high-bleeding risk (HBR) patients. Nonetheless, 12 months of DAPT is the most commonly strategy recommended in patients discharged after an ACS. Methods: We evaluated patterns of DAPT candidates in all patients discharged in single center between 2009 and 2019 after an acute coronary syndrome (ACS). Patients categorized in 3 groups: 1) short-DAPT candidates if they met 1 major o 2 minor criteria for HBR, by the 2019 ARC-HBR criteria; 2) prolonged-DAPT candidates if were not HBR and had recurrent ACS, complex percutaneous coronary interventions or diabetes; 3) standard 12 months DAPT if were not include in the previous 2 groups. We evaluated all-cause and cardiovascular mortality, mayor bleeding (MB), and major cardiovascular events (MACE) after discharge. Results: We assessed 3, 155 patients discharged after an ACS, mean age was 68.4 (13.0), 25.9% were women, 32.5% had diabetes, 13.2% received complex percutaneous coronary interventions and 40.5% were categorized as HBR. After categorization, 1, 277 (40.48%) were candidates for short DAPT, 1, 203 (38.1%) for standard 12m DAPT and 675 (21.39%) for prolonged DAPT. After a median follow-up was 1032 days (interquartile range 555–1950), all-cause mortality was 15.8%, cardiovascular mortality 10.5%, 35.9% had a first MACE and 6.2% had at least one MB. As shown in figure 1, patients candidates for short or prolonged DAPT had significantly higher rates of all-cause and cardiovascular mortality as well as MACE. In contrast, higher rate of MB was only increased in patients candidates for short-DAPT (figure 2). Multivariate analysis demonstrated higher risk of MB (sHR: 1.60 95% CI 1.10–2.60; p=0.030) only in patients candidates for short-DAPT. In contrast, candidates for short-DAPT has higher risk of all-cause mortality (HR: 2.92 95% CI 1.95–4.37; p<0.01) and cardiovascular mortality (HR: 3.01 95% CI 1.78–5.32; p<0.01) and MACE (HR: 2.22, 95% CI 1.82–2.70; p<0.01). Similarly, patients candidates for prolonged DAPT had higher risk of all-cause mortality (HR: 1.72 95% CI 1.10–2.69; p=0.002), cardiovascular mortality (HR: 2.47 95% CI 1.39–4.40; p=0.017) and MACE (HR: 1.58 95% CI 1.28–1.95; p<0.001). Conclusions: Almost two thirds of patients discharged after an ACS would be candidates for short or prolonged DAPT and these patients are at higher risk of MACE and mortality. Patients candidates for short-DAPT had higher risk of MB through the follow-up. These results might reinforce the need of individual assessment of most optimal DAPT duration in all patients discharged after an ACS. Funding Acknowledgement: Type of funding sources: None.